Dependence on ion temperature of shallow-angle magnetic presheaths with adiabatic electrons. (December 2019) - Geraldini, Alessandro; Parra, F. I.; Militello, F.
Abstract : The magnetic presheath is a boundary layer occurring when magnetized plasma is in contact with a wall and the angle [STIX]x1D6FC between the wall and the magnetic field B is oblique. Here, we consider the fusion-relevant case of a shallow-angle, [STIX]x1D6FC1, electron-repelling sheath, with the electron density given by a Boltzmann distribution, valid for [STIX]x1D6FC/[STIX]x1D70F+1m_e/m_i, where m_e is the electron mass, m_i is the ion mass, [STIX]x1D70F=T_i/ZT_e, T_e is the electron temperature, T_i is the ion temperature and Z is the ionic charge state. The thickness of the magnetic presheath is of the order of a few ion sound Larmor radii [STIX]x1D70C_s=m_i(ZT_e+T_i)/ZeB, where e is the proton charge and B=|B| is the magnitude of the magnetic field. We study the dependence on [STIX]x1D70F of the electrostatic potential and ion distribution function in the magnetic presheath by using a set of prescribed ion distribution functions at the magnetic presheath entrance, parameterized by [STIX]x1D70F . The kinetic model is shown to be asymptotically equivalent to Chodura's fluid model at small ion temperature, [STIX]x1D70F1, for |ln [STIX]x1D6FC|>3|ln [STIX]x1D70F|1 . In this limit, despite the fact that fluid equations give a reasonable approximation to the potential, ion gyro-orbits acquire a spatial extent that occupies a large portion of the magnetic presheath. At large ion temperature, [STIX]x1D70F1, relevant because T_i is measured to be a few times larger than T_e near divertor targets of fusion devices, ions reach the Debye sheath entrance (and subsequently the wall) at a shallow angle whose size is given by [STIX]x1D6FC or 1/[STIX]x1D70F, depending on which is largest.